"Chill or thrill": the impact of the "polarity paradox" on hospitality and tourism. Issue 1 (14th March 2016) - De Visser-Amundson, Anna; De Korte, Annemieke; Williams, Simone
Abstract : Purpose: In a society of abundance, complexity, uncertainty and secularisation, consumers seek extreme market offerings. They thereby avoid the grey middle ground and rather seek white or black, or rather utopia or dystopia, in their experiences. This consumer behaviour is coined the Polarity Paradox. The purpose of this paper is to investigate the effect of the Polarity Paradox on travel and tourism and specifically highlight how darker and dystopian type of tourism experiences can add value to the overall tourist experience. Design/methodology/approach: The paper is based on literature and trend report reviews to support the direction of the Polarity Paradox trend and the opportunities it presents to the hospitality and tourism industry. Findings: Travellers do not seek only beauty and happiness when travelling. Examples of the thrilling or dystopian side of the Polarity Paradox clearly illustrate travellers' emerging needs to look for the extreme. In fact, new travel and hospitality experiences are all about originality and understanding that whether the experience triggers positive or negative emotions matter less in a market where consumers want to be "shaken up", surprised, taught something or seek a deeper meaning. The difference with the past is that these same thrill seeking tourists, also seek "white" and chilling experiences and that demands a new approach to market segmentation. Originality/value: Until now, the Polarity Paradox has been described as a general consumer trend. In this paper, the authors are the first to analyse its possible impact on hospitality and tourism and in detail describe that black, dystopian and thrilling experiences can be positive when they trigger emotions and reactions meaningful to the traveller. The authors further show that "playing it safe" will not be the future to build successful hospitality and tourism experiences. The examples explore how the hospitality and tourism industry can add elements of "dystopia" and by doing that actually add value to the overall travel experience.